Conflito de competência em matéria tributária: a questão posta como um ruído comunicacional - Castro, Danilo Monteiro de (2013)
This study aims at the conflict of jurisdiction as to tax matters, observed in the light of Communication Law (the issue is brought up as a communicational noise). Thus, upon a hermeneutic-analytic investigation, the legal system of positive right in law will be analyzed and, therefore, interpreted, so that reflections on the theme are possible according to the communicational perspective in law, and a language with scientific claims. The perspective in question favors the asserting that jurisdiction conflicts are observed (jurisdiction view in law), facilitate the identification of communication noise motivating the phenomenon being studied, enhance the ability to minimize the manifestation of conflicts by inserting infra-constitutional prescriptive statements (jurisdiction rules), and also lead to the analysis on how the conflict should be solved (derivation process), and whom by